PERANCANGAN ULANG TATA LETAK FASILITAS UNTUK MEMINIMALISIR BIAYA MATERIAL HANDLING PADA STUDI KASUS UMKM KONVEKSI ABC - Anggita, Syiera; Purnomo, Hari (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
Poor facility layout is a waste that must be minimized. The layout of MSME Konveksi ABC was studied to reduce OMH (Material Handling Cost) expenses. The messy arrangement of production layouts causes less optimization of the flow of the production process, the occurrence of queues when entering and exiting the production floor, and waste of movement time. This research uses the activity relationship chart (ARC) and activity relationship diagram (ARD) methods to help design efficient and effective layouts by paying attention to the sequence and relationship between production activities. The data used is primary data from conducting interviews with MSME owners. The results of the interview show the need for proposed layout changes with the consideration that each absolute activity needs to be brought closer to its production location, the entry and exit points of the production process are designed separately so that there are no accumulations or obstacles if there are employees who want to enter and will leave simultaneously. The results of the proposed layout show the difference in OMH (Material Handling Costs) between the two existing layouts of Rp 3,341,056.8 so, the proposed layout recommended by researchers to MSME Konveksi ABC provides savings in OMH (Material Handling Costs) expenses and optimizes layouts related to worker effectiveness and efficiency.